ANALYSIS OF THE DEVELOPMENT OF A CULTURAL TOUR PACKAGE AT THE KARO REGENCY'S LINGGA CULTURE VILLAGE - Hetty Claudia Nainggolan (Jurnal Ilmiah Global Education, 2023)
The Covid-19 pandemic has had a significant impact on the tourism industry, including in Indonesia. To develop and thrive, Indonesia has focused on promoting tourism that highlights local culture and knowledge. This research focuses on the Lingga Cultural Tourism Village in Karo Regency as an example of cultural tourism that can be bundled into a tour package. The village features the Karo tribal culture and various attractions, such as the Siwaluh Jabu House, the Cultural Village Museum, and Uruk. However, despite its uniqueness and potential, the tourist sites in the Lingga Cultural Village have not been combined into a comprehensive tour package. This study aims to address the organization of cultural tour packages and the calculation of costs in the Lingga Cultural Village, Karo Regency.The research methodology employed in this study is qualitative. It involves direct observation, structured interviews with local administrators and guides, and the analysis of written records. The findings reveal that the Lingga Cultural Village has great potential as a tourist destination due to its historical and cultural significance. The village offers attractions such as traditional Karo houses, an art studio, a museum, and Uruk. However, the number of hotels and eateries in the area is still limited. The proposed one-day tour package itinerary includes visits to various attractions, such as the Karo Traditional House, art studio performances, Geriten, the Cultural Village Museum, and Uruk. The itinerary is designed to provide international visitors with an immersive experience of Karo culture and history. The calculated selling price for the participants. In conclusion, the research highlights the potential of the Lingga Cultural Village as a cultural tourism destination. The proposed one-day tour package itinerary provides an organized and immersive experience for visitors. The findings contribute to the development of cultural tourism in the region and emphasize the economic and cultural benefits it can bring to the local community.